Nuclear Magnetic Resonance Structure Elucidation of Peptide b2 Ions - Liu, Pengyuan; Cooks, R. Graham; Chen, Hao (Angewandte Chemie International Edition, 2015)
Tandem mass spectrometry (MS/MS) is powerful for chemical identification but it is still insufficient for explicit ion structure determination. A strategy is introduced to elucidate MS fragment ion structures using NMR spectroscopy for the first time. In our experiments, precursor ions are dissociated at atmospheric pressure and the resulting fragment ions are identified by mass spectrometry but collected outside the mass spectrometer, making the subsequent NMR measurements possible. This new strategy has been applied to determine the chemical structure of the characteristic b2 fragment ion, a subject of longstanding debate in MS‐based proteomics. Fragmentation of peptide ions: Atmospheric pressure thermal dissociation‐ (APTD) based preparative mass spectrometry was used to collect gas‐phase peptide b2 fragments for structural elucidation by NMR spectroscopy. This strategy will be applicable to the elucidation of many difficult fragment ion structures in both fundamental ion chemistry studies and in applied proteomics research.